Functional Food Market Development in Serbia: Motivations and Barriers - Stojanović, Žaklina; Dragutinović-Mitrović, Radmila; Ognjanov, Galjina (Industrija, 2013)
The aim of this paper is to present main findings obtained from the empirical analysis of the functional food market in Serbia. The analysis is based on the in-depth interviews with relevant processors and retailers present on the market. The following set of topics are considered: (1) motivations (driving forces) and barriers to offer products with nutrition and health (N&H) claim and (2) perception of consumer demand toward N&H claimed products. Differences between Serbia and other Western Balkan Countries (WBC) are explored by using nonparametric techniques based on the independent samples. Results support overall conclusion that this market segment in Serbia is underdeveloped and rather producer than consumer driven compared to more developed WBC markets.
Keywords: Product; Motivation; Market; Food market; Demand; Consumers